2020
DOI: 10.1111/aab.12593
|View full text |Cite
|
Sign up to set email alerts
|

Salinity stress response of non‐transformed and AtCKX transgenic centaury (Centaurium erythraea Rafn.) shoots and roots grown in vitro

Abstract: Common centaury (Centaurium erythraea Rafn.) is a plant species that can inhabit saline soils. It is known as plant with high spontaneous regeneration potential in vitro. In present work we evaluated shoots and roots salinity tolerance of non transformed and three AtCKX transgenic centaury lines to graded NaCl concentrations (0, 50, 100, 150, 200 mM) in vitro. Overexpression of AtCKX genes in transgenic centaury plants resulted in an altered cytokinins (CKs) profile leading to a decline of bioactive CK levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…Šiler et al [36] described the effects of salinity on the in vitro growth and photosynthesis of centaury shoots. Recently, Trifunović-Momčilov et al [37] showed the physiological and biochemical aspects of the salinity stress response of non-transformed and AtCKX transgenic centaury shoots and roots grown in vitro. It was shown that centaury roots showed a higher salinity tolerance compared to shoots.…”
Section: Introductionmentioning
confidence: 99%
“…Šiler et al [36] described the effects of salinity on the in vitro growth and photosynthesis of centaury shoots. Recently, Trifunović-Momčilov et al [37] showed the physiological and biochemical aspects of the salinity stress response of non-transformed and AtCKX transgenic centaury shoots and roots grown in vitro. It was shown that centaury roots showed a higher salinity tolerance compared to shoots.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to alleviate salinity conditions through the improvement of soil quality (Hasini et al, 2020). However, physiological alterations in plants is also a potential tool to improve tolerance in these environmental conditions because salt stress activates complex downstream signalling pathways (Holm, Hardtke, Gaudet, & Deng, 2001; Trifunović‐Momčilov et al, 2020; Wani et al, 2020). These pathways are primarily related to the increase in ROS, which is associated with oxidative damage in salt‐stressed plants (Akyol, Yilmaz, Uzilday, Özgür Uzilday, & Türkan, 2020).…”
Section: Salt Stressmentioning
confidence: 99%
“…The diversity of morphogenetic paths that C. erythraea can undergo in vitro has been compiled recently [ 28 ]. The vigorous morphogenic potential of the explants favors the use of centaury for genetic transformations [ 29 , 30 , 31 ], interspecific hybridization in vitro [ 32 , 33 , 34 ], functional studies on secondary metabolite synthesis in vitro [ 25 , 26 , 35 , 36 , 37 ], and stress physiology studies [ 38 , 39 ]. Overall, different aspects of C. erythraea’s in vitro development, physiology, pharmacology, and ecology have been studied for over20 years at the Department for Plant Physiology, Institute for Biological Research “Siniša Stanković”, University of Belgrade, resulting in 38 journal papers, 8 book chapters, and 9 masters and doctoral theses.…”
Section: Centuries Of Centaury Researchmentioning
confidence: 99%